1966
DOI: 10.1021/ba-1966-0055.ch028
|View full text |Cite
|
Sign up to set email alerts
|

Phenanthrene Extraction of Bituminous Coal

Abstract: Three bituminous coal samples were extracted at 350°C. with phenanthrene, labeled in one series with tritium, in another with C 14 . The extract yield was 80-90%. Results: converting coal to soluble products breaks C-H bonds; 10-15% of the hydrogen content of the coal exchanged with that of the phenanthrene during extraction; 3-8% chemically linked phenanthrene was found in the extracts; less than 1% hydrogen exchange took place between pure model compounds (anthracene, p-benzyl--phenol) and tritiated phenanth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Some hydrogen exchange was reported for phenanthrene as solvent with coal, but almost no exchange took place with anthracene. 17 In addition, little support was found that the ipso-mechanism was a significant contributor in coal dissolution by 1methylnaphthalene. 18 Yet, naphthalene was capable of reducing the coke from 7.5 ± 0.2% for neat bitumen pyrolysis to 3.8 ± 0.5% for bitumen diluted in naphthalene.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Some hydrogen exchange was reported for phenanthrene as solvent with coal, but almost no exchange took place with anthracene. 17 In addition, little support was found that the ipso-mechanism was a significant contributor in coal dissolution by 1methylnaphthalene. 18 Yet, naphthalene was capable of reducing the coke from 7.5 ± 0.2% for neat bitumen pyrolysis to 3.8 ± 0.5% for bitumen diluted in naphthalene.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This is evident by the fact that the amount of the obtained pitch product was greater than the amount of the organic matter of coal loaded into an autoclave. Ear lier [62], the chemical binding of a solvent (phenan threne) with the products of thermal dissolution of coal was demonstrated by an isotopic marker method. Thus, the introduction of an additional solvent amount is required for performing a process with cir culating solvent.…”
Section: Thermochemical Conversion Of Coals In Solvents Into Liquid Pmentioning
confidence: 99%
“…In previous papers we have outlined a general approach based on interaction forces for the classification of solvents and adsorbents (9,10). This treatment accounts for individual interaction forces in terms of specific solubility parameters which are derived mainly from properties of the pure compounds themselves.…”
Section: Literature Citedmentioning
confidence: 99%
“…One approach which we pursued for the extraction of PAH from these materials was based on the assumption that the strongly adsorbed PAH were insufficiently extractable with benzene (the normal solvent for such extractions). A literature report on the solubilization of a large percentage of a coal sample with refluxing phenanthrene (9) led us to consider higher aromatics as being more likely to extract the PAH. As a first trial we conducted extractions of several carbon black samples with refluxing naphthalene at reduced pressure.…”
mentioning
confidence: 99%